Secure IT systems : 22nd Nordic Conference, NordSec 2017, Tartu, Estonia, November 8-10, 2017, Proceedings /: 22nd Nordic Conference, NordSec 2017, Tartu, Estonia, November 8-10, 2017, Proceedings. (2017) - Unknown
No abstract available